Krim - Erkundungen am Rand Europas - Hofmann, Tatjana (Frank & Timme, 2022)
The Crimean peninsula in the Black Sea, rich in history and charm, is of great geostrategic importance. This leads to political conflicts time and again. But what is everyday life like in Crimea beyond the discourses about law, borders and war? What do local intellectuals think about the situation today? Can Geopoetry help to counteract the current crisis? Tatjana Hofmann's ethnographic long-term observation explores these questions. Her poetic essay, illustrated with magnificent photographs by Alexander Barbuch, transcends the usual boundaries of genre and searches for perspectives far removed from common patterns of interpretation. Tatjana Hofmann, a Slavist and author, lives in Zurich. "Krim - Erkundungen am Rand Europas" continues her 2015 novel "Sewastopologia" continues.